UKURAN LINGKAR PERGELANGAN TANGAN SEBAGAI INDIKATOR KEGEMUKAN PADA ANAK USIA SEKOLAH DASAR DI KOTA BOGOR JAWA BARAT - ., Hermina; Jahari, Abas Basuni (GIZI INDONESIA, 2007)
WRIST CIRCUMFERENCE AS AN INDICATOR FOR OBESITY AMONG PRIMARY SCHOOL CHILDREN IN BOGOR, WEST JAVAIntroduction:Obesity is now increasing problem among primary school children. Obesity duringchildhood has a consequence of obesity in the teen age. Approximately, one third of children withobesity will become obese in their older age.Objective:To examine the reliability of wrist circumference as an indicator of obesity, particularlyfor rapid assessment. Method: The analysis used data from the study on ”The development of nutrition educationintervention for primary school children from midlle economic class families (2001)”. The sample inthis study is primary school children age 9-12 years from several favorite schools in the city ofBogor West Java. The weight and height of 1990 children were collected during the study. Inaddition data of wrist circumference was collected by a simple method non numerical measure buta qualitatif. The method used was by connecting the thumb and the mid-finger of child’s right handon the wrist of child’s left hand. The method gives three condition: 1) Normal if the tips of thumband mid-finger touch each other and no space between wrist and the circle made by the thumband mid-finger, 2) Thin if the tips of thumb and mid-finger touch each other but there is spacebetween the wrist and the circle, and 3) overweight/obese if the tips thumb and mid-finger doesnot touch each other. Data on weight and height were converted into z-score weight-for-height (ZWH) based on WHO-NCHS standard, 1982. Kappa coefficient was obtained to evaluate thereliability of wrist circumference to Z-WH in identifying obesity among school children.Result: 76% of overweight/obese children and 95% of non-overweight/obese children could beidentified by using wrist circumference. The Kappa coefficient for the reliability test is 0,6 and is asufficiently reliable.Conclusion: Wrist circumference could be used as a simple tool for a rapid assesment orsceening of obesity among school children.Keywords:obesity, wrist circumference, weight-for-height Z-score, school children